Aktivitas Guru dan Respons Siswa dalam Pembelajaran Menggunakan Model Make A Match Berbantuan Multimedia - Yuana Citra, Ike Wandira; Fanani, Achmad; Rosidah , Cholifah Tur (Progressive of Cognitive and Ability, 2023)
Low motivation and student learning outcomes are caused by boredom and the notion that science material is difficult to understand. Students are forced to remember and store all kinds of information without connecting it with everyday life. The purpose of this study was to describe the teacher’s activities, student responses, and learning outcomes when the Make A Match model was used in learning natural sciences to transform energy forms with the help of multimedia. The object of this research is the fourth grade students of SDN Simpang, Prambon. The sampling method used purposive sampling technique. The research design uses a descriptive quantitative type approach. The results showed that teacher activity earned a score of 95 in the “Very Good” category, student responses obtained a percentage of 72,3% in the “Good” category, and student learning outcomes with a total of 13 student who completed obtained a percentage of 86,6% in category “Very Good”. So it can be concluded that student learning outcomes and activity can be improved by applying the Make A Match model with the help of the media in learning natural science changes in energy forms.